Current practice in transvenous lead extraction in Latin America: Latin American Heart Rhythm Association survey. (30th July 2021) - Diaz, Juan C.; Romero, Jorge; Costa, Roberto; Cuesta, Alejandro; Biase, Luigi D.; Alviz, Isabella; Velasco, Alejandro; Gabr, Mohamed; Duque, Mauricio; Marin, Jorge E.; Aristizabal, Julian; Velasquez, Jorge; et al.
Abstract: Background: Transvenous lead extraction (TLE) is standard of care for the management of patients with cardiac implantable electronic device infection or lead‐related complications. Currently, objective data on TLE in Latin America is lacking. Objective: To describe the current practice standards in Latin American centers performing TLE. Methods: An online survey was sent through the mailing list of the Latin American Heart Rhythm Society. Online reminders were sent through the mailing list; duplicate answers were discarded. The survey was available for 1 month, after which no more answers were accepted. Results: A total of 48 answers were received, from 44 different institutions (39.6% from Colombia, 27.1% from Brazil), with most respondents (82%) being electrophysiologists. Twenty‐nine institutions (66%) performed <10 lead extractions/year, with 7 (16%) institutions not performing lead extraction. Although most institutions in which lead extraction is performed reported using several tools, mechanical rotating sheaths were cited as the main tool (66%) and only 13% reported the use of laser sheaths. Management of infected leads was performed according to current guidelines. Conclusion: This survey is the first attempt to provide information on TLE procedures in Latin America and could provide useful information for future prospective registries. According to our results, the number of centers performing high volume lead extraction in Latin America is smaller than that reported in other continents, with most interventions performed using mechanical tools. Future prospective registries assessing acute and long‐term success are needed.